A history of modern psychology - Schultz, Duane P. (Academic Press, 1981)
A History of Modern Psychology, 3rd Edition discusses the development and decline of schools of thought in modern psychology. The book presents the continuing refinement of the tools, techniques, and methods of psychology in order to achieve increased precision and objectivity. Chapters focus on relevant topics such as the role of history in understanding the diversity and divisiveness of contemporary psychology; the impact of physics on the cognitive revolution and humanistic psychology; the influence of mechanism on Descartes's thinking; and the evolution of the third force, humanistic psych.